MAKING ENGLISH FUN: INTERACTIVE GAMES FOR YOUNG LEARNERS - Shukurova Sevinch Bahodir qizi; Shamsiddinova Dilafruz (TADQIQOTLAR, 2025)
ABSTRACT This study investigates the usefulness of interactive games for teaching English to young students.  It explores various forms of games, how they impact on language acquisition and the benefits they provide for student engagement. The results indicate that  immersive  games  considerably  improve  vocabulary  memory,  speaking confidence, and overall engagement in language learning.